Nutrient recovery in wastewater treatment plants through biosolids and struvite precipitation: Case study in Panama City - Antonio Santos Sánchez; Karla Santos Oliveira Rodríguez-Esquerre; Diego Lima Medeiros; Aníbal da Fonseca Santiago; Julian David Hunt (Cleaner Water)
This work assesses the nutrient recovery potential in Panama City’s wastewater facilities. Nutrients can be recovered by using biosolids, which are currently dumped in landfills, and by precipitating struvite from waste streams. The economic viability of four types of struvite reactors was analyzed. The installation of struvite systems is not profitable for the current discharge limit of 10 mg/l for P. However, for P limits of 4 mg/l and below, struvite systems would generate significant revenue due to savings in the chemicals needed to remove the excess of P. For a P limit of 4 mg/l, the best struvite reactor presented a payback time of 10 years and a return on investment of 13.68 %. It is concluded that in Panama, as in the rest of Latin American countries, nutrient discharge standards are currently too loose for struvite systems to become viable. Meanwhile, the use of biosolids is of particular interest as the standards for their use are already well developed. The use of biosolids from Panama City could supply 1.6 % of the consumption of fertilizers in the country. It was found that the quality of the biosolids that are produced in the region is satisfactory, and that the demand from potential users can be improved through composting the material.